Candesartan modulates microglia activation and polarization via NF-κB signaling pathway. (November 2020) - Qie, Shuyan; Ran, Yuanyuan; Lu, Xiaosheng; Su, Wei; Li, Wei; Xi, Jianing; Gong, Weijun; Liu, Zongjian
Microglia are diverse cells that acquire different functional phenotypes in response to microenvironment in which they reside. Several transcriptional regulators have been identified that regulate different microglia phenotypes. They are mainly stimulated into two opposing phenotypes, classically (M1) and alternatively (M2) phenotype. Regulating microglia polarization from M1 to M2 state has been suggested as a potential therapeutic approach in treatment of CNS disorders. Candesartan, an angiotensin II type I receptors antagonist, exerts beneficial effects for antioxidant, anti-inflammation, neurotrophic, and anti-apoptotic function. However, the effect of candesartan on microglia polarization and underlying mechanisms remain unknown. In this study, the resting microglia were stimulated to M1 microglia with lipopolysaccharide (LPS) and interferon-γ (IFN-γ), and then treated with vehicle or candesartan for 24 h. RT-PCR was utilized to detect the mRNA expression of microglia phenotype markers and inflammatory cytokines. Microglia phenotype markers and toll-like receptor 4 (TLR4)/nuclear factor kappa B (NF-κB) pathway were determined by western blot. A neuron-microglia co-culture system was used to determine whether candesartan could ameliorate the neurotoxic effect of M1 microglia to oxygen-glucose deprivation (OGD) neuron. Candesartan treatment reduced the expression of M1 markers, and increased M2 markers. Meanwhile, candesartan reduced fluorescence intensity and protein level of M1 marker and enhanced M2 marker. Candesartan also regulated the neuroinflammatory response via reducing the release of pro-inflammatory cytokines and increasing anti-inflammatory cytokines in LPS + IFN-γ stimulated BV2 cells. Candesartan markedly inhibited the protein level of TLR4, the phosphorylation of IKBα and p65, and suppressed nuclear translocation of NF-κB p65. BAY 11-7085, a NF-κB inhibitor, remarkably enlarged the inhibitory effect of candesartan on NF-κB pathway. In addition, M1 phenotype microglia exacerbated post-OGD N2a cells death and LDH release, whereas candesartan reversed such neurotoxic effect. Candesartan treatment may ameliorate stroke-induced neuronal damage through shifting microglia to M2 phenotype in a TLR4/NF-κB-dependent manner.